Advances in quality control through the development of a more sustainable and eco-friendly direct spectrophotometric method than pharmacopoeial methods for the determination of bisoprolol fumarate - Safwan Ashour (Drug Analytical Research)
A sustainable eco-friendly direct spectrophotometric method was developed and validated for the estimation of bisoprolol fumarate (BF) in the marketed dosage form. BF in an aqueous medium of 0.10 N NaOH exhibits a maximum absorption at 273 nm that permits its direct estimation by zero-order spectrophotometric method without any interference in a linear range of 1.66–190.0 μg mL-1 (r = 0.9999, n = 5) with detection and quantitation limits were 0.211 and 0.638 μg mL-1, respectively. The suggested method was successfully adopted to evaluate BF in bulk and tablets. The technique showed adequate precision, with a relative standard deviation value lower than 1.78%. Excellent values of accuracy were obtained, with a recovery mean value of 100.37%. The results indicated that the proposed method is highly efficient in determining the amount of BF in the tablets, which helps improve quality control and environmental improvement. Furthermore, the greenness and whiteness profile of the method was evaluated using different evaluation metrics; AES, AGREE, AGREEprep, GAPI, BAGI, and RGB12. The proposed spectrophotometric method was more sustainable, eco-friendly, efficient, productive, and practical than the reported HPLC-UV methods (BP and USP), as confirmed by the absence of consumption of chemical reagents and polluting organic solvents, reduced analysis stages, energy consumption, analysis time and low cost, making it a safer alternative to be considered.